A new recursive Simpson integral algorithm in vibration testing - Xu, Jingbo; Xu, Xiaohong; Cui, Xiaomeng (Australian journal of mechanical engineering, 2021)
In vibration testing, the time domain integral is a key issue. A kind of recursive Simpson integral method is presented in this paper, which combines Newton-Leibniz formula and 3/8 Simpson formula to obtain the recurrence integral calculation of each point. The integrated waveform of whole sequence can be obtained by polynomial fitting and detrended processing. The verification test is carried out through the earthquake data provided by MATLAB and frequency domain analysis, which illustrates the effectiveness of this method. Furthermore, the method has high computational precision and efficiency, its truncation error reaches 4 order infinitesimal of sampling interval, and is suitable for vibration testing application.